Ageism and lookism as stereotypes of health disparity in intensive care units in Iran: a critical ethnography - Sajad Yarahmadi; Mohsen Soleimani; Mohammad Gholami; Ali Fakhr-Movahedi; Seyed Mohsen Saeidi Madani (BMC, 2024)
Abstract Background The intensive care unit presents structural complexities, and the prevailing power imbalance between patients and staff can lead to health disparities. Hence, unveiling the underlying factors that give rise to and reinforce these disparities can contribute to their prevention. This study aims to shed light on the stereotypes linked to ageism and lookism, which perpetuate health disparities within the intensive care unit setting in Iran. Methods This critical ethnographic study employed Carsepkan's approach and was carried out in intensive care units in the west of Iran from 2022 to 2023. The data collection and analysis were conducted through three interconnected stages. In the initial stage, more than 300 h of observations were made at the research site. In the subsequent stage, a horizon analysis was performed. Conversations with 14 informants were conducted in the final stage to enrich the dataset further. Then the analysis process was carried out as in the previous step to uncover an implicit culture of health disparity. To verify the validity and reliability of the study, credibility, conformability, dependability, and transferability were all taken into account. Findings The ageism and lookism stereotypes emerged from seven main themes; youth-centric; negative ageism; age-friendliness; age-related priority; centered care for pediatric patients and families; appearance-centeredness; and a contradiction between belief and behavior. Conclusion This critical study showed that ageism and lookism stereotypes permeated the intensive care unit's culture. These stereotypes have the potential to influence equality dynamics, as well as to foster and support health disparity in the intensive care unit.